Walk on water [videorecording (DVD)] - Fox, Eytan, 1964-; Ashkenazi, Lior; Berger, Knut; Peters, Caroline. (Writer on Christianity) (Sony Pictures Home Entertainment, 2005)
While on assignment in Berlin, an Israeli intelligence agent is tasked with offing a Nazi war criminal. However, he has a crisis of consciousness after he befriends a target's gay grandson.